2017
DOI: 10.1002/pds.4262
|View full text |Cite
|
Sign up to set email alerts
|

Impact of clinical evidence communications and drug regulation changes concerning rosiglitazone on prescribing patterns of antidiabetic therapies

Abstract: The most frequently added AD in diabetes patients who had switched off rosiglitazone in 2010 was pioglitazone, followed by DPP-4 inhibitors. Despite new evidence from a long-term clinical trial and the Food and Drug Administration's subsequent decision to eliminate access restrictions on rosiglitazone in 2013, domestic regulations were left intact; hence, its use remained negligible in Korea.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 22 publications
(45 reference statements)
0
14
0
Order By: Relevance
“…Over the last decade, DPP-4 inhibitors have achieved a substantial uptake in prescription volume, and they have overtaken SUs as the most preferred add-on to metformin since 2014 in Korea. 3 In the current analysis, among incident users of DPP-4 inhibitors, a tendency more toward treatment addition rather than switches to alternative therapy was observed, which could be understood in the context of their favorable safety and tolerability profile. Despite the growing preference for DPP-4 inhibitors in clinical practice, in our analysis, they were evaluated as inferior to metformin in delaying the first-treatment adjustment when used as initial monotherapy.…”
Section: Discussionmentioning
confidence: 66%
See 3 more Smart Citations
“…Over the last decade, DPP-4 inhibitors have achieved a substantial uptake in prescription volume, and they have overtaken SUs as the most preferred add-on to metformin since 2014 in Korea. 3 In the current analysis, among incident users of DPP-4 inhibitors, a tendency more toward treatment addition rather than switches to alternative therapy was observed, which could be understood in the context of their favorable safety and tolerability profile. Despite the growing preference for DPP-4 inhibitors in clinical practice, in our analysis, they were evaluated as inferior to metformin in delaying the first-treatment adjustment when used as initial monotherapy.…”
Section: Discussionmentioning
confidence: 66%
“… 20 Of note is that TZD agents analyzed in our study were primarily pioglitazone as rosiglitazone’s use became almost nonexistent post the severe access restrictions on the latter TZD agent in late 2010 in Korea due to increased, albeit controversial, CV risk. 3 TZD therapy may improve insulin sensitivity and reduce the rate of decline in β-cell function, and these features might be effective in delaying monotherapy failure by positively influencing the durability of the therapeutic effect. 7 , 21 Nevertheless, the findings in the present study did not support the durability of TZD-based initial monotherapy as demonstrated in the previous study.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the mechanisms by which DPP-4 inhibitors induce NRF2 activity are largely unknown. Considering that they have largest prescription volume among the new antidiabetic drug classes ( Ahren, 2008 ; Phung et al ., 2010 ; Noh et al ., 2017 ), the recent findings regarding their potential NRF2-modulatory effects are of significant importance for patients with diabetes who are chronically exposed to the respective antidiabetic therapy and who are at increased risk of developing malignant complications because of underlying disease. Although the mechanisms of DPP-4 inhibitors’ effects on NRF2 activation remain elusive, it might be beneficial to use a DPP-4 inhibitor in combination with metformin in diabetes patients who also have cancer as a comorbidity.…”
Section: Nrf2 Inhibitors For Cancer Therapy: a Repurposing Approachmentioning
confidence: 99%